SOPO BATAK TOBA RESILIENCE TECTONICS TOWARD EARTHQUAKE STUDY OBJECT: SOPO NAGARI SIHOTANG - Chandra (Jurnal Riset Arsitektur, 2019)
Abstract- Sopo is a granary house in traditional Batak Toba architecture. Sopo is important for Batak Toba community because it serves as a place to store rice which is the source of life. Nowadays sopo is harder to find than ruma. Most of the sopo has transformed into Batak Toba house and uses as a residence. Sopo is located in Lake Toba, North Sumatra, which is prone to earthquakes. Sopo Nagari Sihotang was built in the 1920s and has experienced many earthquakes, now the sopo still survive without any structural damage. The resistance of the sopo over the years proves the sopo resilience to earthquakes. From the evidence of resilience to earthquake, its interesting to investigate the tectonics of this sopo. The purpose of the research is to understand the tectonic of Sopo Nagari Sihotang that resilience to earthquake and find local wisdom in facing earthquake disaster.The research used descriptive method with qualitative approach by describing the existing state of Sopo Nagari Sihotang and comparing it with tectonic theory and earthquake resistant structure. The sopo’s data were collected by field observation and literature study. The data are grouped into four parts, namely construction, detail, space, and ornaments that become points for analysis of tectonics. Tectonic analysis is associated with the theory of earthquake resistant structures to find out what makes tectonic of the sopo resilient to earthquakes.The result is the tectonic resilience of the Sopo Nagari Sihotang to earthquakes are found in the tectonics construction in the use of materials; tectonics detail on vertical structures and horizontal structures; and tectonics space at the story height – the activity, the spatial form – the building hape, the spatial form - the structure, and the activity - the structure. The tectonic resilience of Sopo Nagari Sihotang to earthquakes is not found in the tectonics construction and tectonics ornament. The local wisdom which are the main factors make the sopo resilience to earthquake are found on, the tectonics detail of the sopo post-batu ojahan can retain the sopo by relying on the frictional force resulting from self-weight of the sopo; the tectonics detail of the sopo post-ransang can bind every sopo posts; the use of lightweight wood materials thus reducing inertia forces. Key Words: resilience, tectonics, sopo, earthquake, Batak Toba